The Antarctic ozone hole during 2014 - Krummel, PB; Klekociuk, AR; Tully, MB; Gies, HP; Alexander, SP; Fraser, PJ; Henderson, SI; Schofield, R; Shanklin, JD; Stone, KA (Journal of Southern Hemisphere Earth Systems Science, 2020)
We review the 2014 Antarctic ozone hole, making use of a variety of groundbasedand space-based measurements of ozone and ultra-violet radiation, supplementedby meteorological reanalyses. While the polar vortex was relatively stablein 2014 and persisted some weeks longer into November than was the case in2012 or 2013, the vortex temperature was close to the long-term mean in Septemberand October with modest warming events occurring in both months, preventingsevere depletion from taking place. Of the seven metrics reported here, allwere close to their respective median values of the 1979-2014 record, beingranked between 16th and 21st of the 35 years for which adequate satellite observationsexist.